Reducing 50% sodium chloride in healthier jerked beef: An efficient design to ensure suitable stability, technological and sensory properties. (June 2019) - Vidal, Vitor A.S.; Biachi, João P.; Paglarini, Camila S.; Pinton, Mariana B.; Campagnol, Paulo C.B.; Esmerino, Erick A.; da Cruz, Adriano G.; Morgano, Marcelo A.; Pollonio, Marise A.R.
Abstract: The objective of this study was to evaluate the effects of the partial replacement of NaCl by blends of KCl and CaCl2 on the physicochemical, microbiological, and sensory properties of jerked beef. For that, in the dry and wet salting stages, 50% NaCl of the control treatment (FC1) was replaced by 50% KCl (F1), 50% CaCl2 (F2), and a blend containing 25% KCl and 25% CaCl2 (F3) at equivalent concentrations based on the ionic strength. All reformulated treatments presented a significant sodium reduction when compared to the control (27.57% F1, 41.59% F2, and 36.74% F3). The CaCl2 blends resulted in final products with bitter taste and rancid aroma accompanied by a higher TBARS and shear force and lower a* values ( P <   .05 ). The substitute salts did not affect the microbiological stability ( P >   .05 ). The present results demonstrate that adding 50% KCl may be a good strategy to reduce sodium in jerked beef. Highlights: 50% NaCl was replaced by blends of KCl and CaCl2 to reduce sodium in jerked beef. Blends with CaCl2 increased bitter taste and rancid aroma in reformulated jerked beef. Reduced sodium product stability was maintained with blends of CaCl2 and KCl. KCl was the best salt substitute to preserve sensory properties of reduced sodium jerked beef.